2009
DOI: 10.1073/pnas.0908786106
|View full text |Cite
|
Sign up to set email alerts
|

Age-related hearing loss in C57BL/6J mice is mediated by Bak-dependent mitochondrial apoptosis

Abstract: Age-related hearing loss (AHL), known as presbycusis, is a universal feature of mammalian aging and is the most common sensory disorder in the elderly population. The molecular mechanisms underlying AHL are unknown, and currently there is no treatment for the disorder. Here we report that C57BL/6J mice with a deletion of the mitochondrial pro-apoptotic gene Bak exhibit reduced age-related apoptotic cell death of spiral ganglion neurons and hair cells in the cochlea, and prevention of AHL. Oxidative stress indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
304
3
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(330 citation statements)
references
References 50 publications
(72 reference statements)
18
304
3
2
Order By: Relevance
“…These findings may support the possibility that ubiquinol-10 has anti-aging effects, because ubiquinone-10 is readily reduced to ubiquinol-10 after dietary uptake (33,63) and a ratio of ubiquinol-10 to total CoQ10 of more than 85% is maintained in the plasma (40,70). Dietary supplementation with ubiquinol-10 produces beneficial effects for several agerelated diseases, such as cardiovascular disease, diabetes, agerelated hearing loss (AHL), and Parkinson's disease (50,61,62,68). Our recent study identified many ubiquinol-10-sensitive genes that are regulated by peroxisome proliferatoractivated receptor-alpha (PPARa) in the liver (54).…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…These findings may support the possibility that ubiquinol-10 has anti-aging effects, because ubiquinone-10 is readily reduced to ubiquinol-10 after dietary uptake (33,63) and a ratio of ubiquinol-10 to total CoQ10 of more than 85% is maintained in the plasma (40,70). Dietary supplementation with ubiquinol-10 produces beneficial effects for several agerelated diseases, such as cardiovascular disease, diabetes, agerelated hearing loss (AHL), and Parkinson's disease (50,61,62,68). Our recent study identified many ubiquinol-10-sensitive genes that are regulated by peroxisome proliferatoractivated receptor-alpha (PPARa) in the liver (54).…”
Section: Introductionsupporting
confidence: 54%
“…3 and 4). Previous studies showed that the mean ABR hearing threshold at low frequencies was significantly lower in ubiquinone-10-supplemented control mice (61,62). Similar to SAMP1 mice, ubiquinone-10 suppressed AHL in C57BL/6J mice by increasing antioxidant activities via SIRT3 activation.…”
mentioning
confidence: 91%
“…Studies have shown that CR delays the onset of AHL and reduces cochlear pathology (141,150) by reducing oxidative stress (150), which plays a major role in AHL (73,149). Notably, SIRT3 is required for the beneficial effect of CR in preserving auditory function.…”
Section: Sirt3 Prevents Hearing Loss During Crmentioning
confidence: 99%
“…Şimdiki çalışmalar VOR in oluşturulması için uygun elektik stimulasuyon modelini bulmak ve VOR' deki adaptif mekanizmaları geliştirmek üzerine odaklanmıştır (56). Kulakta bulunan saç hücrelerinin yenilenmesini teşvik etmek için geliştirilen vestibuler protezler, genetik olarak gentamisin duyarlılığnın tespiti, kulaktaki saçlı hücre kaybı için alfa lipoik asit coenzyme Q10 gibi anti oksidan kullanımı gündemde olan tedavilerdir (57,58).…”
Section: İki Tarafli Vestibulopatide Vestibuler Rehabilitasyonunclassified